PENGARUH KUALITAS PRODUK, GAYA HIDUP, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI KOTA SURABAYA - Aurelia, Jessie; Wriyakusuma, I Gusti Bagus Yosia (PERFORMA, 2022)
Technology has developed rapidly and fast in recent era, and people have considered smartphones as necessity that cannot be separated from daily life. Annually the number of smartphone users gets increased and the competition of smartphone manufacturers gets tighter and tougher. A lot of criminal cases that occur in Indonesia are committed to get smartphones. Apple Inc. company is one of the leading companies in the world technological sector and has successfully become the most precious brand in the world for 13 years. The smartphone of iPhone itself has become the leader of smartphones in the world. This research is done to find out the effect of product quality, lifestyle, and brand image on purchase decision of iPhone in Surabaya city. This research uses quantitative approach with non-probability sampling technique and purposive sampling method. The number of samples that is used in this research is as 160 iPhone users who domicile in Surabaya. In this research, multiple linear regression analysis is done by using SPSS program. The result shows that the variables of product quality, lifestyle, and brand image affect positive and significant on purchase decision of iPhone in Surabaya city. Those three independent variables simultaneously affect purchase decision. The implication of the result of this research is expected to assist Apple company to find out the viewpoint of iPhone consumers especially iPhone users in Surabaya city. The company is expected to be able to adapt with the product or strategy that can be implemented in Indonesia because from those three independent variables that are analyzed, there are several things that need to be improved and maintained by Apple company. Keywords: iPhone, product quality, lifestyle, brand image, purchase decision